Optimalisasi Konsentrasi Protease dari Pepaya untuk Produksi Minyak Kelapa - Silvera Devi; Itnawita ' (Universitas Riau, 2009)
Coconut oil was produced by using enzyme protease of latex from bird papaya fruit with concentration from 0,1% to 15%. Protease was gained from bird papaya fruit and protease effectivity was identified from some analysis parameters according to SNI No 01-3741-1995 for cooking oil and SNI No. 01-2902-1992 for coconut oil. Optimum concentration of protease recovery was found at 1,5%, 29% (v/v) oil number; 0,24% (w/w) water content; 0,1% (w/w) impurities content; 7,6% (w/w) iodine number; 250,5% saponification content; 1,1% peroxide number; 4.45% (w/w) free fatty acid. The coconut oil has fulfill the National-Atandard analysis (SNI).